Academic Performance and Achievement of Selected Track Athletes - Sullivan, Margie; Jackson, Jr., E. Newton (My University, 2001)
Data on all first time in college (FTIC) track athletes at a major southeastern university over a ten-year period (1983-1993) were examined to compare variables of gender, ethnicity, admission scores (high school grade point average and SAT/ ACT scores), terminal academic major, graduation rates, and cumulative university grade point averages with those FTIC in the general student body. Reports generated from the university's student database and data from the Registrar's Office were examined. Data for the non-revenue student-athlete group was comprised of 115 or 44.9% females and 141 or 55.1% males for a total of 256 (see Table 1). The general student body data, contained 34,068 students of whom 19,491 or 57.2% were female and 14,577 or 42.8% were male. Results of this descriptive and exploratory study may provide valuable information to academic and athletic communities that may help to debunk myths of student-athletes, guide policy, and improve programs. The mean university GPA for the student body was higher (2.63) compared to track/cross country student-athletes (2.56). Track/cross country students (69.9%) had a higher graduation rate compared to the general student body (64.5%).
Keywords: track/cross country; non-athlete students; academic performance; graduation